Comparison of the Fungal Community, Chemical Composition, Antioxidant Activity, and Taste Characteristics of Fu Brick Tea in Different Regions of China - Chen, Yulian; Chen, Jiaxu; Chen, Ruyang; Xiao, Leike; Wu, Xing; Hu, Lin; Li, Zongjun; Wang, Yuanliang; Zhu, Mingzhi; Liu, Zhonghua; Xiao, Yu (Frontiers in Nutrition, 2022)
In this study, the fungal community structure, metabolites, antioxidant ability, and taste characteristics of five Fu brick tea (FBT) from different regions of China were determined and compared. A total of 69 operational taxonomic units (OTUs) were identified and assigned into 5 phyla and 27 genera, with Eurotium as the predominant genus in all samples. Hunan (HN) sample had the strongest fungal diversity and richness, followed by Guangxi (GX) sample, and Zhejiang (ZJ) sample had the lowest. GX sample had higher amounts of gallic acid (GA), total catechins, gallocatechin (GC), and epicatechin gallate (ECG) as well as antioxidant activity than the other samples. The levels of total phenolics, total flavonoids, epigallocatechin (EGC), catechin, epicatechin (EC), thearubigins (TRs) and theaflavins (TFs) were the highest in the ZJ sample. Guizhou (GZ) and Shaanxi (SX) samples contained the highest contents of epigallocatechin gallate (EGCG) and gallocatechin gallate (GCG), respectively. Total phenolics, GA, EC, CG, and TFs were positively associated with most of fungal genera. Total phenolic content (TPC), total flavonoid content (TFC), and most of catechins contributed to the antioxidant activities of FBT. HN sample had the strongest sourness and sweetness, ZJ sample had the strongest saltiness, SX sample had the strongest umami, and GZ sample had the strongest astringency, which was ascribed to the varied metabolites. This work reveals that FBT in different regions vary greatly in fungal community, metabolites, antioxidant activity, and taste characteristics, and provides new insight into the quality characteristics formation of FBT in different regions.